2021
DOI: 10.1371/journal.pone.0259455
|View full text |Cite
|
Sign up to set email alerts
|

Joint transcriptomic and metabolomic analysis reveals the mechanism of low-temperature tolerance in Hosta ventricosa

Abstract: Hosta ventricosa is a robust ornamental perennial plant that can tolerate low temperatures, and which is widely used in urban landscaping design in Northeast China. However, the mechanism of cold-stress tolerance in this species is unclear. A combination of transcriptomic and metabolomic analysis was used to explore the mechanism of low-temperature tolerance in H. ventricosa. A total of 12 059 differentially expressed genes and 131 differentially expressed metabolites were obtained, which were mainly concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…But in our study, HRW treatment inhibited the accumulation of coniferyl alcohol and eriodictyol, which may be due to the redirection of metabolic fluxes in branches of the phenylpropane pathway in response to cold stress. Zhuang et al (2021) indicated that the coniferyl alcohol content of H. vernicosa increased, which indicated that the antioxidant system of H. vernicosa was activated and coniferyl alcohol was synthesized to improve its cold tolerance. This result is contrary to our findings, so we speculate that differences in plant species and abiotic stress types may be responsible for this contradiction.…”
Section: Discussionmentioning
confidence: 99%
“…But in our study, HRW treatment inhibited the accumulation of coniferyl alcohol and eriodictyol, which may be due to the redirection of metabolic fluxes in branches of the phenylpropane pathway in response to cold stress. Zhuang et al (2021) indicated that the coniferyl alcohol content of H. vernicosa increased, which indicated that the antioxidant system of H. vernicosa was activated and coniferyl alcohol was synthesized to improve its cold tolerance. This result is contrary to our findings, so we speculate that differences in plant species and abiotic stress types may be responsible for this contradiction.…”
Section: Discussionmentioning
confidence: 99%
“…Sinapyl alcohol is among the precursors of lignin, which is associated with water and solute transport and cell wall rigidity, and contributes to abiotic stress resistance (Lee et al, 2021). Hosta ventricosa enhances its cold resistance by adjusting the ratio of sinapyl alcohol to coniferyl alcohol, thereby altering the morphological structure of the cell wall (Zhuang et al, 2021).…”
Section: Phenylpropanoid Biosynthesis Involved In Cold Resistancementioning
confidence: 99%
“…In contrast to CaM and CBL, which have to couple with Ca 2+ to change their conformation and be activated, CDPKs, which are constitutively activated and directly phosphorylated, transduce calcium signals by interacting with the site of the calcium receptor or forming a peptide chain [ 62 ]. CDPKs are involved in the intermediate process instead of participating in the initial response to low temperature in rice.…”
Section: Molecular Mechanisms Of Crosstalk Between Ca 2+ ...mentioning
confidence: 99%